Outcomes in frail patients receiving BCMA-directed bispecific antibodies for relapsed/refractory multiple myeloma - Benjamin Adegbite; Carlyn Rose Tan; Tala Shekarkhand; Ross S. Firestone; Eric M. Jurgens; Kevin Miller; Alexander M. Lesokhin; Gunjan L. Shah; Neha Korde; Sridevi Rajeeve; Heather J. Landau; Michael Scordo; et al. (Blood Advances)
Abstract: Patients with relapsed/refractory (R/R) multiple myeloma (MM) are often frail with preexisting comorbidities and poor performance status (PS). To evaluate clinical characteristics and outcomes based on frailty, we conducted a single-center retrospective study of patients with R/R MM who received B-cell maturation antigen (BCMA)–directed bispecific antibodies (BsAbs). Frailty was defined using the simplified frailty index based on age, Eastern Cooperative Oncology Group (ECOG) PS, and Charlson comorbidity index (CCI; nonfrail score 0-1 and frail score ≥2). Of 102 patients analyzed (age range, 40-88 years), 40 (39%) were considered frail. The frail group had more patients aged ≥70 years (73% vs 29%; P < .001), with ECOG PS ≥2 (36% vs 0%; P < .001), and worse median CCI (2 vs 1; P < .001). Patients in the frail group experienced similar rates of all-grade cytokine release syndrome (58% vs 60%; P = .99), immune effector cell–associated neurotoxicity syndrome (15% vs 8%; P = .44), and treatment-related mortality (13% vs 21%; P = .27) compared to the nonfrail group. The best overall response rate was 80% (stringent complete response [sCR]/CR, 15%; very good partial response [VGPR], 48%) in the frail group vs 73% (sCR/CR, 23%; VGPR, 31%) in the nonfrail group (P = .40). With a median follow-up of 8.6 months (range, 3-14), there was no significant difference in median progression-free survival (not reached vs 11 months; P = .051) or overall survival (37 vs 25 months; P = .37) between the frail and nonfrail groups. Hence, BsAbs were deemed safe and effective for older and frail patients with R/R MM.